The economics of GM food labels: An evaluation of mandatory labeling proposals in India - Bansal, Sangeeta; Ramaswami, Bharat (International Food Policy Research Institute, 2007)
Labeling of genetically modified (GM) foods is a contentious issue and internationally, there is sharp division whether such labeling ought to be mandatory. This debate has reached India where the government has proposed mandatory labeling. In this context, this paper evaluates the optimal regulatory approach to GM food labels. Mandatory labeling aims to provide greater information and correspondingly more informed consumer choice. However, even without such laws, markets have incentives to supply labeling. So can mandatory labeling achieve outcomes different from voluntary labeling? The paper shows that this is not the case in most situations. The paper goes on to explore the special set of circumstances, where mandatory labeling makes a difference to outcomes. If these outcomes are intended, mandatory labeling is justified; otherwise not.